Staff training in physical interventions: a literature review - McDonnell, Andrew A.; O’Shea, Marion C.; Bews-Pugh, Stephanie J.; McAulliffe, Hannah; Deveau, Roy (Frontiers in Psychiatry, 2023)
Background Restrictive practices are used frequently by frontline staff in a variety of care contexts, including psychiatric hospitals, children’s services, and support services for older adults and individuals with intellectual and developmental disabilities. Physical restraint has been associated with emotional harm, physical injury to staff and consumers, and has even resulted in death of individuals in care environments. Various interventions have been implemented within care settings with the intention of reducing instances of restraint. One of the most common interventions is staff training that includes some physical intervention skills to support staff to manage crisis situations. Despite physical intervention training being used widely in care services, there is little evidence to support the effectiveness and application of physical interventions. This review will examine the literature regarding outcomes of staff training in physical interventions across care sectors. Method A systematic search was conducted following PRISMA guidelines using Cochrane Database, Medline EBSCO, Medline OVID, PsychINFO, and the Web of Science. Main search keywords were staff training, physical intervention, physical restraint. The MMAT was utilised to provide an analytical framework for the included studies. Results and discussion Seventeen articles have been included in this literature review. The included studies take place in a range of care settings and comprise a wide range of outcomes and designs. The training programmes examined vary widely in their duration, course content, teaching methods, and extent to which physical skills are taught. Studies were of relatively poor quality. Many descriptions of training programmes did not clearly operationalise the knowledge and skills taught to staff. As such, it is difficult to compare course content across the studies. Few papers described physical interventions in sufficient detail. This review demonstrates that, although staff training is a ‘first response’ to managing health and safety in care settings, there is very little evidence to suggest that staff training in physical intervention skills leads to meaningful outcomes.